«ҚОБЛАН» ДӘСТАНЫНДА ЭПИКАЛЫҚ САНЛАР СИСТЕМАСЫ - Палымбетов, К.С. (FAN va JAMIYAT, 2020)
The article is about the use of the system of epic numbers in the compostition of the Karakalpak folk dastan “Koblan”. It is emphasized the role of numbers in revealing the ideological content and poetic artistry of the dastan.